Developing Christology for Ethnic Minorities in North America: An Attempt to Find the Historical Jesus in the Multicultural-Pluralistic-Multilingual Context - Heo, Chun-Hoi (Toronto journal of theology, 2008)
Korean immigrants who are living as an ethnic minority in North America call into question traditional Western portraits of Jesus that have been developed only from the perspective of dominant cultures. During the last decades, the historical Jesus has been predominantly located in the first-century Galilean setting, in which Jesus surely lived and taught, by so-called historical Jesus scholars such as Sean Freyne, J.D. Crossan, Richard A. Horsley and Burton Mack. Although their contribution is illuminating in terms of discovering the historically more primitive and culturally more open figure of the historical Jesus, they cannot avoid the accusation that their approach to the historical Jesus has been dominated by a religiously mono cultural and monolithic-monolingual perspective.